1) х+х/10=-11/2 2) 3(2х-1)-5(7-х)=8(1-х)-3(х+5) х+2\3+4-5х/4=-2 срочно надо пожалуйста.))))))))))))))))) спасибо за решение

1) х+х/10=-11/2 2) 3(2х-1)-5(7-х)=8(1-х)-3(х+5) х+2\3+4-5х/4=-2 срочно надо пожалуйста.))))))))))))))))) спасибо за решение
Гость
Ответ(ы) на вопрос:
Гость
 1) х+х/10=-11/2      11x/10=-11/2       11x=-55          x=-5 2) 3(2х-1)-5(7-х)=8(1-х)-3(х+5)      6x-3-35+5x=8-x-3x-15       6x+5x+3x=8-15+35        14x=28         x=2 3.  х+2\3+4-5х/4=-2       x+4 2/3-1 1/4x=-2        -1/4x=-2-4 2/3=-6 2/3         x=-6 2/3:-1/4          x=26 2/3          
Не нашли ответ?
Ответить на вопрос
Похожие вопросы